2017
DOI: 10.1007/s11746-016-2944-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fatty Acid Composition on Transportation Fuel Yields via the Non‐Catalytic Cracking of Triacylglyceride Oils

Abstract: A wide spectrum of triacylglyceride (TG) oils were decomposed in batch lab and continuous pilot‐scale reactors to generate an extensive database, which was then used to construct a model to predict the detailed composition of products generated during non‐catalytic cracking. The model was then coupled with additional simulated process steps to determine the yields of transportation products and other chemical co‐products meeting specifications of their petroleum analogs as validated with laboratory testing. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The situation was changed by overexpression of TaFAE1 under the control of 8UAS-pTEF in YL62 when C18:1Δ 9 dropped from over 50% to less than 30% of TFA in cells. This was accompanied by a more than 2-fold increase in palmitoleic acid (C16:1Δ 9 ) and an important increase in all VLCFA. The most profound change in fatty acid profile was seen in strain YL53, where the major fatty acid became C16:1Δ 9 instead of the usual C18:1Δ 9 .…”
Section: Fatty Acid Profiles Of Vlcfa-producing Strainsmentioning
confidence: 98%
See 2 more Smart Citations
“…The situation was changed by overexpression of TaFAE1 under the control of 8UAS-pTEF in YL62 when C18:1Δ 9 dropped from over 50% to less than 30% of TFA in cells. This was accompanied by a more than 2-fold increase in palmitoleic acid (C16:1Δ 9 ) and an important increase in all VLCFA. The most profound change in fatty acid profile was seen in strain YL53, where the major fatty acid became C16:1Δ 9 instead of the usual C18:1Δ 9 .…”
Section: Fatty Acid Profiles Of Vlcfa-producing Strainsmentioning
confidence: 98%
“…This was accompanied by a more than 2-fold increase in palmitoleic acid (C16:1Δ 9 ) and an important increase in all VLCFA. The most profound change in fatty acid profile was seen in strain YL53, where the major fatty acid became C16:1Δ 9 instead of the usual C18:1Δ 9 . Behenic (C22:0), C22:1Δ 13 , and lignoceric (C24:0) acids were the most accumulated VLCFA in YL53.…”
Section: Fatty Acid Profiles Of Vlcfa-producing Strainsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous work reporting the noncatalytic cracking of crop oils in a continuous pilot scale system has shown that, under low‐pressure conditions, a significant fraction of the liquid product is obtained in the form of 1‐alkenes (Seames et al, ). The 1‐tetradecene and other C 14 –C 17 terminal alkenes, which are formed as a result of the deoxygenation or cleavage of C 16 and C 18 fatty acids, may be valuable feedstocks.…”
Section: Introductionmentioning
confidence: 99%
“…1‐Tetradecene was selected as the feedstock as this is a representative compound for the longer carbon chain‐length alkenes generated during cracking (Seames et al, ). The primary objective of this work was to determine if these longer‐chain 1‐alkenes, as represented by the model compound 1‐tetradecene, can be efficiently converted into aromatics, and whether the aromatic products’ speciation and homology profile would be different compared to those obtained with lighter alkenes.…”
Section: Introductionmentioning
confidence: 99%